Online resources and learner autonomy - Oktavia Widiastuti (UPT P2M Politeknik Negeri Malang, 2013)
There is a perceived relationship between technology and learner autonomy in the language teaching community. Students become increasingly empowered when using technology as they develop self-discipline and confidence through increased responsibility for their own learning processes. For language learning, computers offer rich volumes of text, pictures, sound, and video, they are also interactive, available at any time and place for individual or collective learners. It also facilitates learner autonomy, which is understood as the learner’s learning capacity displayed both in the way the learner learns and in the way he or she transfers what has been learned to wider contexts. It involves the learner, teacher, materials, learning context, and what students want in an online environment. Online learning offers many opportunities for students. Some research results showed that the students responded positively to this means of communication. The students’ way of learning interaction is enriched through the computerized media. Furthermore, it can enhance their learning as it strengthens their understanding toward the language they learn and their self study, meaning that it makes this type of language learners more motivated than the non-autonomous ones. At present, however, there is a great need for research that focuses on the relationship between particular forms of practice and the development of autonomy to support the theoretical assumptions.